Fondasi Ecological-Philosophy dengan Model Place-Based Education untuk Clinical Legal Education - Mohammad Alvi Pratama; Virly Vidiasti Sabijanto; Eva Laila Rizkiyah (Yustitiabelen, 2022)
Human misdeeds and the absence of legislative acknowledgement of environmental integrity cause environmental devastation. Historically, anthropocentric views of law have resulted in laws that serve as instruments to tame and manage nature, with nature existing solely as a means to an end: human welfare (in terms of human rights). As a legal instrument, it might be considered a natural legitimacy that destroys the environment, particularly via anthropocentric power relations. Environmental law is still biased in favor of human wellbeing rather than ecological integrity. As a result of this study, it is necessary to design an extra learning model for Clinical Legal Education (CLE) based on the Ecological Philosophy paradigm that supports the Deep Ecology perspective with the Pedagogy of Place-Based Education (PBE) Model. This study uses a qualitative descriptive-analytical approach to highlight the situation and legal requirements. The outcomes of this study indicate that the prevalence of the anthropocentric paradigm in law results in clinical legal education that is similarly anthropocentrically constrained. Connectivity while activity exists solely between humans. Therefore, CLE requires one more model to be liberated. The PBE paradigm successfully connects humans with their ecological surroundings. This relationship must adhere to the ecological paradigm. Therefore, the ecological philosophy foundation supplied can enhance students' environmental consciousness. So that in clinical legal education activities, students are ecologically aware and may encourage access to environmental justice.